Recommendations for the use of active personal dosemeters (APDs) in interventional workplaces in hospitals. (July 2021) - O'Connor, U.; Carinou, E.; Clairand, I.; Ciraj-Bjelac, O.; De Monte, F.; Domienik-Andrzejewska, J.; Ferrari, P.; Ginjaume, M.; Hršak, H.; Hupe, O.; Knežević, Ž.; Sans Merce, M.; et al.
Highlights: Active Personal Dosimeters (APDs) are now increasingly used in hospitals. A series of APD tests was completed by EURADOS (European Radiation Dosimetry) group. This has informed our summary on the state-of-the-art of APDs, and the challenges. Users should take care with APD readings in pulsed radiation fields. Our recommendations will make the use of APDs more reliable and meaningful. Abstract: Occupational radiation doses from interventional procedures have the potential to be relatively high. The requirement to optimise these doses encourages the use of electronic or active personal dosimeters (APDs) which are now increasingly used in hospitals. They are typically used in tandem with a routine passive dosimetry monitoring programme, with APDs used for real-time readings, for training purposes and when new imaging technology is introduced. However, there are limitations when using APDs. A survey in hospitals to identify issues related to the use of APDs was recently completed, along with an extensive series of APD tests by the EURADOS Working Group 12 on Dosimetry for Medical Imaging. The aim of this review paper is to summarise the state of the art regarding the use of APDs. We also used the results of our survey and our tests to develop a set of recommendations for the use of APDs in the clinical interventional radiology/cardiology settings, and draw attention to some of the current challenges.